The effects of visual stimulation on the cortical activity of brainstem stroke dysphagia patients: A functional near-infrared spectroscopy study - Dandan Zhao; Yancun Li; Keyi Ning; Bingjie Zou; Bin Wang; Libo Li; Qiaojun Zhang; Yanping Hui (PLoS ONE, 2025)
Objective To investigate the difference in cortical activity under food visual stimulation between patients with brainstem stroke dysphagia and healthy adults by using functional near-infrared spectroscopy (fNIRS). Additionally, we seek to identify any potential relationship between cortical activity and swallowing. Methods 30 patients with dysphagia after brainstem stroke and 16 healthy adults were selected. The fNIRS was used to assess the functional connection strength of global and ROIs brain regions at rest, as well as the mean change in oxygenated hemoglobin concentration (ΔHbO2) during the food visual stimulation task in both groups. Results In the resting state, the functional connection strength of healthy adults (X―=0.514, s=0.021) was higher than that of patients (X―=0.472, s=0.009) (P < 0.05). In comparison, functional connectivity in the ROI brain region was enhanced in the patient group compared to the healthy adult group. In the task state, the patient’s ΔHbO2 concentration in the left Frontopolar area, right Frontopolar area, left Orbitofrontal area and left Dorsolateral prefrontal cortex dramatically decreased in comparison to the healthy adult group. The correlation analysis revealed a moderate negative correlation between SSA and the MMSE score, VAS score, and the average ΔHbO2 concentrations in specific brain regions, including the right Frontopolar area, left Frontopolar area, left Orbitofrontal area, and left DLPFC. Furthermore, the VAS scores exhibited a moderate positive correlation with the average ΔHbO2 concentrations in the right Frontopolar area, left Frontopolar area, left Orbitofrontal area, and left DLPFC. Conclusion Patients with brainstem stroke dysphagia showed reduced activity during visual stimulation in the Frontopolar region, the left Orbitofrontal area, and the left Dorsolateral prefrontal cortex as compared to healthy individuals. The overall strength of functional connections was decreased, while the ROI between different brain areas increased. Following a brain stem stroke, all of these might be related to pre-oral swallowing issues.